ADSORPTION-PHOTOCATALYSIS SYNERGY OF BI4TI2.9FE0.1O12 FOR CIPROFLOXACIN REMOVAL - Hikmah, Nurul; Prasetyo, Anton (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The triple-layer Aurivillius compound Bi4Ti2.9Fe0.1O12 has been reported to exhibit both adsorption and photocatalytic properties and, therefore, can be used to remove organic waste such as antibiotic residues. In this study, the Bi4Ti2.9Fe0.1O12 compound was synthesized using the molten salt method. The diffractogram showed Bi4Ti2.9Fe0.1O12 compound was successfully synthesized with no impurity phases detected. Scanning electron microscopy (SEM) images revealed that the compound has a plate-like/sheet-agglomerated particle morphology, with sizes ranging from 2 to 6 μm. Band gap energy calculations showed that the Bi4Ti2.9Fe0.1O12 compound has a band gap of 2.74 eV (453 nm). Adsorption tests demonstrated that the compound could adsorb 54.47± 0.56% of ciprofloxacin. Adsorption-degradation tests over 30, 60, 90, and 120 minutes reduced ciprofloxacin c oncentration by 59.84±0.54, 64.05±0.056, 70.04±0.091, and 62.55±0.052%, respectively. It indicates that the adsorption mechanism is more dominant than the photocatalytic mechanism. This may be due to the large number of ciprofloxacin molecules adhering to the BIT surface, making it difficult for light to penetrate, thereby preventing the photocatalytic mechanism from operating at its maximum efficiency.